Integrating Zebrafish Model to Screen Active Ingredients and Network Pharmacology Methods to Explore the Mechanism of Lavandula angustifolia Therapy for Alzheimer's Disease. Issue 28 (22nd July 2022) - Li, Muchun; Cao, Xueqin; Yan, Huan; Wang, Miaomiao; Tashibolati, Ayiguli; Maiwulanjiang, Maitinuer
Abstract: Lavandula angustifolia (LA) is a traditional Chinese herbal medicine commonly used as a folk medicine to treat brain diseases; in previous pharmacological studies, its water extract has been reported to have neuroprotective effects with the potential to be used in the treatment of Alzheimer's disease (AD). However, the material basis and the action mechanism of the effects were not clear. Hence, we have adopted a fast, low‐cost strategy to address this problem, through the following three processes: degreased lavender flower grains are extracted stepwise, main active sites are screened by zebrafish AD model, and key compounds and major pathways are identified using network pharmacology tools. The initial results show luteolin‐7‐glucoside, Apigenin‐7‐O‐glucoside, Salvianolic acid A and Rosmarinic acid can be used as the main active ingredient for lavender treatment of Alzheimer's disease. The major biological processes involved in these compounds include regulation of defense responses, decomposition of extracellular matrix, oxidative stress response, and peptidyl tyrosine phosphorylation. The most important metabolic pathways are cancer, IL‐17 signaling and age‐rage signaling indiabetic complications. Therefore, the strategies developed in this study are helpful to address the unclear material basis and mechanism of the effect of Chinese herbal medicine as well as form a bridge between traditional Chinese herbal medicine and modern medical language. Abstract : This study included gradient extraction of water extracts from defatted lavender flowers, screening of active sites using zebrafish AD model, qualitative analysis of compounds in active sites using high resolution mass spectrometry, and identification of four key compounds and their functional pathways using network pharmacology tools. It is a fast, low‐cost method that helps researchers screen active compounds from complex plant extracts: these compounds may not have been directly related to alzheimer's disease treatment in previous studies.